DEVELOPMENT EXPERIMENTAL SETUP PROCESS MODELING UPHOLDING OF THE JET AVIATION FUEL IN THE COMMODITY RESERVOiRS REFUELING - A. N. Kozlov; M. L. Nemchikov (Научный вестник МГТУ ГА, 2016)
The article discusses the laboratory setup option for modeling separation of mechanical impurities in ground fuel tanks before refueling aircraft.